FORMULASI DAN EVALUASI GRANUL EKSTRAK ETANOL RIMPANG KUNYIT (Curcuma longa L.) DENGAN METODE GRANULASI BASAH - Karsani Egalisa; Angga Cipta Narsa; Lisna Meylina (PROSIDING SEMINAR KIMIA, 2025)
Turmeric Rhizome (Curcuma longa L.) is a plant from the Zingiberaceae family that is commonly used as a food coloring and fragrance. Turmeric rhizome extract which has the chemical content of turmeric, including curcuminoid compounds, provides benefits as a medicine for body health. This study aims to develop a granule preparation containing turmeric rhizome extract (Curcuma longa L.), determine the physical properties of the resulting granules and determine the level of panelist preference for the turmeric rhizome extract granule preparation. Granules are made using the wet granulation method, the mass of the resulting granules is then evaluated with several tests such as: organoleptic test, flow rate test, angle of repose test, density and compressibility test, water content test, and granule size distribution test. The resulting granules have a slight turmeric odor and a yellowish color from the extract and are in the form of coarse granules. The turmeric rhizome extract formula meets the requirements for flow rate, angle of repose, compressibility, water content, but for the granule size distribution test it does not meet the requirements. Turmeric rhizome extract was formulated into a granular preparation with the results of the flow rate test of 17.85 g/second, angle of repose of 17.21º, compressibility index value of 13.2%, water content of 3.63%, particle size distribution value produced a percentage of fines of 38.18% indicating a percentage of fines that did not meet the requirements. And the level of panelists' preference for the preparation of turmeric rhizome extract granules can be accepted well. Keywords: Turmeric Rhizome, Wet Granulation, Evaluation of Granular Preparations.